2016
DOI: 10.1093/icvts/ivw359
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in a patient on extracorporeal membrane oxygenation with infective endocarditis, pericarditis and heparin-induced thrombocytopenia

Abstract: Heart failure patients with pacemaker or defibrillator-associated endocarditis in cardiogenic shock have few treatment options. We present a case of an INTERMACS I patient who developed device infection, sepsis, bacterial pericarditis and heparin-induced thrombocytopenia. The patient was stabilized with extracorporeal membrane oxygenation and successfully transplanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…No significant bleeding was mentioned. Chen et al reported a 55‐year‐old man who developed HIT while on ECMO because of cardiogenic shock. After HIT was suspected (and later confirmed), anticoagulation with bivalirudin was initiated without any adverse effects.…”
Section: Treatment Of Hitmentioning
confidence: 99%
“…No significant bleeding was mentioned. Chen et al reported a 55‐year‐old man who developed HIT while on ECMO because of cardiogenic shock. After HIT was suspected (and later confirmed), anticoagulation with bivalirudin was initiated without any adverse effects.…”
Section: Treatment Of Hitmentioning
confidence: 99%
“…H-PF4 antibody enzyme-linked immunosorbent assay (ELISA) was performed as a screening test for HIT (13,14), where optical density (OD) values of equal to or greater than 0.4 was considered positive. Following a positive screening test, the diagnosis was usually confirmed by either functional assays, such as serotonin release assay (SRA) (6,8,(15)(16)(17) or heparin induced platelet aggregation assay (HIPA) (5,18,19), or a strong clinical suspicion of HIT with subsequent recovery of thrombocytopenia following heparin discontinuation (8,10,(20)(21)(22)(23)(24). High positive ELISA test result (e.g., OD >1.0) alone was sometimes considered sufficient to confirm the diagnosis of HIT (6,25).…”
Section: Definitionsmentioning
confidence: 99%
“…Nineteen unique cases of heart transplantation in the setting of active IE derived from 14 publications were included in our analysis . The median age was 44 years (23‐64 years).…”
Section: Resultsmentioning
confidence: 99%
“…The other patient had undergone prior HT . One patient had a nonischemic cardiomyopathy and coexisting heparin‐induced thrombocytopenia . Finally, one patient had a history of a valved conduit for aortic stenosis, an ascending aortic aneurysm complicated by decreased systolic function, and complete heart block requiring pacemaker placement.…”
Section: Resultsmentioning
confidence: 99%